Matrix Designs and Methods for Secure and Efficient Compressed Sensing - Cambareri, Valerio <1986> (Alma Mater Studiorum - Università di Bologna, 2015)
The idea of balancing the resources spent in the acquisition and encoding of natural signals strictly to their intrinsic information content has interested nearly a decade of research under the name of compressed sensing. In this doctoral dissertation we develop some extensions and improvements upon this technique's foundations, by modifying the random sensing matrices on which the signals of interest are projected to achieve different objectives.